(untitled) (European Journal of Education and Psychology, 2008)
The present study examined differences among four categories of adolescents –aggressors, pure victims, aggressive victims, and students not involved in behavioural or victimization problems at school– with respect to self-esteem, depressive symptomatology, perceived stress, feeling of loneliness, and a general measure of satisfaction with life. Participants were 1,319 adolescents aged from 11 to 16 years old (47% male) and drawn from seven state secondary schools in Valencia (Spain). Analyses of variance revealed significant differences between the four categories of students. Thus, adolescents not involved showed general better psychosocial adjustment; they had higher levels of self-esteem and satisfaction with life, and lower levels of depressive symptomatology, perceived stress and feeling of loneliness. The scores for this group were equivalent to those of aggressors with respect to self-esteem, depressive symptomatology and loneliness. However, aggressors perceived more stress and expressed less satisfaction with life, as did the other two groups, namely pure victims and aggressive victims. Victims reported the strongest feelings of loneliness. Key words: Aggressor, victim, aggressive victim, school violence, psychosocial adjustment.